O conto de Josué Guimarães para leitores em formação - Frizon, Josué Rodrigues (2015)
This text aims to present and discuss some aspects related to the formation of new readers in the school environment. The descriptive and bibliographical research, developed by applying the action- research with a qualitative approach, had as theme a tale of a south Brazilian writer called Josué Guimarães and reflected on a reading mediation involving three tales of that writer. The mediation was held with the participation of two groups of 1st year of high school from a private education system, located in a central town of the state of Rio Grande do Sul. The work is based on Maria da Glória Bordini e Vera Teixeira de Aguiar (1988) theoretical assumptions related to readers formation. Therefore, we observe the target public reception in relation to the Guimarães work, which resulted in an experience of producing stories by the students. The structure of this work presents, in the frist chapter, some observations and findings about reading problems faced by educational institutions, as well as the reading low scores in Brazil. In the second chapter presents the life story of Josue Guimarães, and the characteristics of his short texts the tales in particular, the narrative, O cavalo cego. The third chapter provides the planning of the reading mediation and also the whole methodology applied in the practices. Finally, in the fourth chapter, we present a memorial with questions answered by participantes of the activity, and spontaneous comments, as well as ten of the stories written by the students, this material prove the efficiency of the activity developed. We conclude by emphasizing the importance of the meaningful mediations with literary texts, with the aim of forming new readers, using the environment`s literary collection